A Novel Hydrolytic Activity of Tri-Functional Geranylgeranyl Pyrophosphate Synthase in Haematococcus pluvialis. (20th August 2018) - Lao, Yong Min; Jin, Hui; Zhou, Jin; Zhang, Huai Jin; Zhu, Xiao Shan; Cai, Zhong Hua
Abstract: Under environmental stresses, Haematococcus pluvialis accumulates large amounts of carotenoids. Scale of carotenoid biosynthesis depends on availability of geranylgeranyl pyrophosphate (GGPP) precursor, which is supplied by GGPP synthase (GGPPS) through sequential 1′-4 condensation of three isopentenyl pyrophosphates (IPPs) into dimethylallyl pyrophosphate (DMAPP). Using IPP and DMAPP as substrates, a tri-functional HpGGPPS was identified in this study to promiscuously synthesize allylic prenyl pyrophosphates (PPPs), e.g. C10 geranyl pyrophosphate (GPP), C15 farnesyl pyrophosphate (FPP), and C20 GGPP. Intriguingly, HpGGPPS can utilize GPP or FPP as a single substrate to synthesize GGPP by hydrolyzing the allylic PPP substrate into C5 IPP. Transcription of HpGGPPS and key carotenogenesis genes, morphological transformation, and carotenoid biosynthesis were differentially induced by environmental stresses, while HpGGPPS's products were low in vivo, implying that most of PPP flux had been shunted into carotenoid biosynthesis. Hydrolyzing allylic PPP intermediates into C5 building blocks by promiscuous HpGGPPS may be a fail safe for carotenoid accumulation against environmental stress.